2005
DOI: 10.1146/annurev.energy.30.081804.121028
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMICS OF POLLUTION TRADING FOR SO2AND NOX

Abstract: ▪ Abstract  For years economists have urged policy makers to use market-based approaches such as cap-and-trade programs or emission taxes to control pollution. The sulfur dioxide (SO2) allowance market created by Title IV of the 1990 U.S. Clean Air Act Amendments represents the first real test of the wisdom of economists’ advice. Subsequent urban and regional applications of nitrogen oxides (NOx) emission allowance trading took shape in the 1990s in the United States, culminating in a second large experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 71 publications
1
73
0
Order By: Relevance
“…There is an active private market for the trading of NOx 2 These characteristics of the commodities that were to be auctioned are discussed in section II 3 In more inelastic demand environments the clock auctions become relatively less advantageous for revenue generation. 4 For an excellent synopsis of this and related programs see Burtraw et al (2005 Each state has a NOx emissions budget, and has considerable flexibility in allocating its budgeted emission allowances to sources. In Virginia, allowances specific to their year of issuance are allocated to firms for whom NOx emissions are a byproduct of production.…”
Section: Background Informationmentioning
confidence: 99%
“…There is an active private market for the trading of NOx 2 These characteristics of the commodities that were to be auctioned are discussed in section II 3 In more inelastic demand environments the clock auctions become relatively less advantageous for revenue generation. 4 For an excellent synopsis of this and related programs see Burtraw et al (2005 Each state has a NOx emissions budget, and has considerable flexibility in allocating its budgeted emission allowances to sources. In Virginia, allowances specific to their year of issuance are allocated to firms for whom NOx emissions are a byproduct of production.…”
Section: Background Informationmentioning
confidence: 99%
“…These have suggested that the gains from trade are huge, with cost-savings that in some cases exceed 90 percent of the abatement costs compared to 'command-and-control' (Tietenberg, 1992. See also Carlson et al, 2000;Burtraw et al, 2005). However, compared with observed abatement, they find that only parts of the potential savings are realized.…”
Section: Introductionmentioning
confidence: 98%
“…The crucial development was the start of sulphur-dioxide trading in the US in 1995 (for which see, especially, Ellerman et al, 2000 andBurtraw et al 2005). It had been known for twenty years or more that damage to the environment and to human health was being caused by sulphur-dioxide emissions, notably from coal-fired power stations, which react in the atmosphere to produce 'acid rain' and other acid depositions.…”
mentioning
confidence: 99%
“…Allowance prices of $400 a ton were predicted, but in fact prices averaged around $150 or less in the early years of the scheme. The flexibility that trading gave to utilities helped to reduce costs (by around a half compared to having to meet a standard that imposed a uniform maximum emission rate: see Ellerman et al, 2000 andBurtraw et al, 2005) but other factors were equally important.…”
mentioning
confidence: 99%